Rav Nahman and Rav Sheshet. Conflicting methods of exegesis of tannaitic sources - Cohen, Barak S. (2005)
Rav Nahman and Rav Sheshet, who lived in the early fourth century C.E., are two of the most prominent Babylonian amoraim. They are known for their numerous disagreements, having conflicting opinions on halakhic issues in over thirty five instances in both Talmuds. The present study presents a systematic analysis of the entire corpus of their disagreements revealing significant differences in their system of study and exegesis, primarily with regard to the use and interpretation of tannaitic sources. Their diverse approaches originate from differing methods of study: Rav Sheshet had a conservative approach, employing formalistic exegesis of tannaitic sources, while Rav Nahman employed an innovative technique, tending to expand tannaitic sources through creative interpretation. Moreover, there is a clear relationship between the data derived from an analysis of their respective methodologies and the rest of their literary legacy in talmudic literature. Indeed, the examination of the methodologies of Rav Nahman and Rav Sheshet demonstrates the importance of the careful examination of the collective corpus of amoraic literature. Ultimately this is the key to building a coherent intellectual history of the amoraim.
Keywords: Rabbinismus